Borrowing Benefits: Group Treatment With Clinical Emotional Freedom Techniques Is Associated With Simultaneous Reductions in Posttraumatic Stress Disorder, Anxiety, and Depression Symptoms - Dawson Church PhD; Dennis House PhD (SAGE Publishing, 2018)
Clinical Emotional Freedom Techniques (EFT) is an evidence-based treatment for depression and anxiety. The current study sought to elucidate the relationship between posttraumatic stress disorder (PTSD), depression, and anxiety in a nonclinical population. The sample (N = 81) comprised participants at five 2-day EFT workshops. All groups used an EFT protocol called Borrowing Benefits, in which the group facilitator works with a single client while other participants self-apply EFT. Participants were assessed on 9 specific conditions as well as on the breadth (Positive Symptom Total [PST]) and depth (General Symptom Index [GSI]) of psychological distress. Physical pain and addictive cravings were also assessed. Significant reductions were observed in all measures (P < .03). Associations between PST, GSI, and PTSD were significant (P < .026). Participants maintained all gains at 6-month follow-up (P < .02) with the exception of the Hostility subscale, while Cohen's d = 0.54 indicated a moderate treatment effect for PTSD. The relationship between psychological and physiological conditions identified in this study is consistent with that found in other studies. Group treatment is cost-effective and efficient, and the efficacy of EFT in groups indicates the utility of the Borrowing Benefits technique.